Evidence of repeated Late Holocene subsidence in the SE Cyclades (Greece) deduced from submerged notches. - Evelpidou, N.; Melini, D.; Pirazzoli, P.; Vassilopoulos, A. (International Journal of Earth Sciences, 2014)
An underwater geomorphological survey along the coasts of six Cycladic islands (Sifnos, Antiparos, Paros, Naxos, Iraklia and Keros) revealed widespread evidence of seven submerged tidal notches. At least seven former shorelines were identified at depths between 280 ± 20 and 30 ± 5 cm below modern sea level. The vertical succession of several submerged notches suggests the occurrence of rapid subsidence events, potentially of seismic origin. Comparison with other sea-level indicators from Naxos and Delos islands indicates that these relative sea-level changes took place after 3300 BP and provides a rough estimate of the time of development of several submerged shorelines. The submergence of the uppermost notch at −30 ± 5 cm is ascribed to effects of the recent global sea-level rise occurred during the last two centuries and, at least in part, to effects of recent earthquakes. Potential effects of the 1956 Amorgos earthquake with regard to coseismic and post-seismic vertical displacement have been recently investigated using a modellistic approach. According to the above, the lower shorelines should result from repetitive subsidence events and not from gradual subsidence.